Jablines Le Haut Château (Seine-et-Marne) Une minière de silex au Néolithique - Bostyn, Françoise; Lanchon, Yves (Documents d'archéologie française, 1992)
This volume is the first of the series "Archéologie et grands travaux", created within the DAF series to welcome the publication of large scale rescue excavations, and in part financed by developers of projects in rural or urban situations. Discovered during excavations carried out before construction work on the northern TGV line, the site of jablines uncovered a neolithic flint mine which became the object, for the first time in France, of large scale excavation. More than 1 000 features had been located and 58 shafts completly explored. The results of these studies conducted by a pluridisplinary team are presented here in detail. Finally, the site is placed within its regional environment and compared to sites of the same type in France and the rest of Europe.